2021
DOI: 10.1021/acs.inorgchem.1c02322
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Properties of Common Bioinorganic Ligands with Switchable Variants of Cytochromec

Abstract: Ligand substitution at the metal center is common in catalysis and signal transduction of metalloproteins. Understanding the effects of particular ligands, as well as the polypeptide surrounding, is critical for uncovering mechanisms of these biological processes and exploiting them in the design of bioinspired catalysts and molecular devices. A series of switchable K79G/M80X/F82C (X = Met, His, or Lys) variants of cytochrome (cyt) c was employed to directly compare the stability of differently ligated protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that mutations in the Ω-loop D (70–85) such as K72A, P76C, K79G/M80X, I81A, F82K, and V83G may alter the heme crevice dynamics and ligand-binding properties. 19 , 32 , 40 42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that mutations in the Ω-loop D (70–85) such as K72A, P76C, K79G/M80X, I81A, F82K, and V83G may alter the heme crevice dynamics and ligand-binding properties. 19 , 32 , 40 42 …”
Section: Resultsmentioning
confidence: 99%
“…The faster rate of the azide binding to the heme of I81N h Cyt c may suggest the faster dissociation of the Met80-heme ligation. Previous studies have shown that mutations in the Ω-loop D (70–85) such as K72A, P76C, K79G/M80X, I81A, F82K, and V83G may alter the heme crevice dynamics and ligand-binding properties. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The unfolding profiles for the M66H and M167H in both ferric and ferrous states display two separate transitions (Figure ). Studies of M80H cyt c have revealed that the stability of the His-ligated protein decreases only slightly in the ferric state, but drops dramatically in the ferrous state compared to the stability of the Met-ligated WT . With this knowledge, we assign the first unfolding transition to be of the c 4 -B domain in both ferric variants.…”
Section: Resultsmentioning
confidence: 92%
“…Studies of M80H cyt c have revealed that the stability of the His-ligated protein decreases only slightly in the ferric state, but drops dramatically in the ferrous state compared to the stability of the Met-ligated WT. 36 With this knowledge, we assign the first unfolding transition to be of the c 4 -B domain in both ferric variants. Assuming then that the His-ligation does not change much the stability of ferric c 4 -A and c 4 -B, the unfolding order of the two domains in M66H and M167H is the same as that in ferric WT c 4 .…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation